Gothic/Giallo/Genre: hybrid images in Italian horror cinema, 1956-82 - Brown, Keith H (2012)
Italian horror cinema is commonly divided into two periods and genres. An initial classical Gothic period spanned the years from 1956 to 1966 and was followed by a modern giallo (thriller) period from 1970 to 1982. Whilst accepting this broad distinction, this paper seeks to add nuance by considering the hybrid elements of three key films by three of the most important directors working in the giallo and horror area, namely Riccardo Freda with I Vampiri (1956), Mario Bava with The Girl Who Knew too Much (1963) and Dario Argento with Deep Red (1975). Drawing in particular upon Nöel Carroll’s idea of “fearing fictions”, I contend that Freda’s film, the first Italian horror movie since the silent era, is notable for being a distinctively modern vampire film; that Bava’s film, a foundational giallo, may be seen as having a palimpsest in Jane Austen’s Gothic parody Northanger Abbey; and that Argento’s film, while often taken as the paradigmatic giallo, has supernatural horror elements that push it in the direction of the Gothic.